2005
DOI: 10.1007/bf02893037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E on the platelet xanthine oxidase and lipid peroxidation in the patients of myocardial infarction

Abstract: Platelets play important role in precipitating ischaemic myocardial syndromes in many ways. One of the consequences of ischaemic diseases is excessive generation of oxygen derived free radicals that have numerous pathophysiological consequences. Platelet pro-oxidant enzyme, xanthine oxidase is one of the sources of generation of free radicals. In the present paper, we report the effect of administration of vitamin E along with aspirin on the levels of platelet xanthine oxidase and extent of free radical mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Damage of the existing enzymes so as to exhibit reduced activities by the high levels of free radicals generated during reperfusion appears to be more probable. This view is further supported by the observation that administration of anti-oxidants such as vitamin E and C for a short time to the patients significantly restores the decreased levels of the enzymes back to near normal values and decreases the levels of MDA generation [27,28].…”
Section: Discussionmentioning
confidence: 72%
“…Damage of the existing enzymes so as to exhibit reduced activities by the high levels of free radicals generated during reperfusion appears to be more probable. This view is further supported by the observation that administration of anti-oxidants such as vitamin E and C for a short time to the patients significantly restores the decreased levels of the enzymes back to near normal values and decreases the levels of MDA generation [27,28].…”
Section: Discussionmentioning
confidence: 72%
“…During ischemic conditions, the adenosine nucleotide pool is degraded to hypoxanthine and xanthine, along with conversion of xanthine dehydrogenase to xanthine oxidase (6,7). Xanthine oxidase acts on xanthine and hypoxanthine with the resultant production of oxygen free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Under ischemic conditions, there is depletion of ATP and subsequent loss of membrane Ca 2+ gradient. Increased Ca 2+ levels activates Ca 2+ dependent proteases which cause selective proteolysis of the dehydrogenase to convert it into xanthine oxidase which acts both on hypoxanthine and xanthine at the expense of molecular oxygen to produce superoxide ion (6,7). Thus xanthine oxidase in ischemic conditions of the heart, as in myocardial infarction, may play an important role in contributing free radical mediated damage.…”
mentioning
confidence: 99%
“…The second line of defense to ROS is provided by antioxidant compounds present in the body such as thiols, or taken from outside such as α-tocopherol, β-carotenoids, flavonoids and L-arginine. We have earlier shown that administration of vitamin C10,11 and vitamin E12,13 to the patients of ischemic myocardial syndromes lower lipid per-oxidation, increase the activities of free radical scavenging enzymes, which are decreased in these patients, and lower the activity of pro-oxidant enzyme which are elevated in the patients. Oxidized low density lipo-proteins are involved in the progression of atherosclerotic lesions14 which can be prevented by L-arginine administration.…”
Section: Introductionmentioning
confidence: 99%